Bacteriophage conjugated IRMOF-3 as a novel opto-sensor for S. arlettae. (10th August 2016) - Bhardwaj, Neha; Bhardwaj, Sanjeev K.; Mehta, Jyotsana; Nayak, Manoj K.; Deep, Akash
Abstract : This article reports the novel assembly of a bacteriophage-based fluorescent sensor for the selective and sensitive detection of a model bacterium ' Staphylococcus arlettae ( S. arlettae )'. Abstract : This article reports the novel assembly of a bacteriophage-based fluorescent sensor for the selective and sensitive detection of a model bacterium ' Staphylococcus arlettae ( S. arlettae )'. A host specific bacteriophage was bioconjugated with a fluorescence metal organic framework 'IRMOF-3'. Changes in the photoluminescence intensities of this fluorescent probe were correlated with bacterial concentrations. The proposed bacteriophage based opto-sensor provided a low detection limit (100 cfu mL −1 ) along with specificity in the detection with respect to other some non-specific bacteria, e.g. S. aureus and E. coli . The detection was achieved over a wide range of bacterial concentrations, i.e. 10 2 –10 10 cfu mL −1 S. arlettae . Compared to antibody and DNA based optical sensors, the use of bacteriophage in conjugation with IRMOF-3 should offer advantages of simplicity and stability. The use of IRMOF-3 as a fluorescent molecule should also offer the development of reproducible sensors because of its well defined structural geometry and hierarchical assembly.